COMMON EUROPEAN UNION ENERGY POLICY ON THE MAKING AND THE INTERESTS OF LITHUANIA - Vaičiūnas, Žygimantas (Politologija, 2015)
Common energy policy of the European Union is one of the most intensively developing EU integration fields. Still on the integration agenda of the EU the energy policy as such appeared just recently – the main principles of the EU energy policy were laid down during 2005 and 2006 and currently this issue is one of the topical problems in various EU summits. Lithuania as the other states of Central and Eastern Europe has unique opportunity to participate actively in the process of the EU energy policy developments. Two different processes – the beginning of the EU membership and genesis of the EU energy policy – started simultaneously. According to this coincidence Lithuania has an unique opportunity to participate in the formation of the EU energy policy from its birth. Lithuania perceives EU energy policy the key instrument for increasing its energy security. Consequently Lithuania is interested in adoption of EU energy policy according its priorities. The aims of this article are to evaluate the benefit of the EU energy policy for Lithuania, review the main elements of this policy as well as assess Lithuania’s influence on EU energy policy. EU energy policy considering its content is multi-dimensional because it involves plenty of energy issues: creation of common internal market, increasing the security of supply, environmental problems, development of renewable energy sources, increasing of energy efficiency, technology developments, etc. Lithuania’s interests in the agenda of the EU energy policy can be summarized in two main principles: 1) the formation of the consistent EU energy policy as soon as it is possible; 2) widening of the EU energy policy agenda including the principles of the security of supply, European neighbourhood policy and other areas. The analysis of the main EU energy policy strategy documents indicates that EU energy policy is developing in favourable direction to Lithuania’s interests. Moreover, recent EU energy policy strategy documents are more practically applicable while ensuring energy security of Lithuania comparing with the previous documents that mostly were orientated towards identification of energy security problems without offering solutions how to overcome it. Energy security problems of Baltic states, identified in 2006 at the European Commission energy Green Paper in 2009 were transformed to the particular plans how these problems could be solved. One of the recent EU energy policy document – Baltic Energy Market Interconnection Plan – is unprecedented activity by its regional form and its particularly clear and binding content. These developments for the first time of the EU energy policy history demonstrates that EU already drew the trajectory of its energy policy and currently is moving towards the implementation stage of the main energy policy options. Four main achievements can be identified showing that EU energy policy develops accordingly to the main Lithuania energy policy interests: 1) deepening and widening consideration for the external dimension of the EU energy policy; 2) comprehensive attitude towards the phenomenon of energy isolation of the Baltic states; 3) the integration of the EU energy policy towards other areas of EU integration; 4) increasing significance for the principle of security of supply. Concluding statement of the article is that the priorities of the EU and Lithuania energy policy are converging. This fact can be qualified as the success of Lithuanian European policy indicating that Lithuania managed to transform its national energy policy interests towards priorities of the EU energy policy.